Antihyaluronidase and Alkaline Phosphatase (ALP) Activities of Medicinal Plants to Combat Echis carinatus Venom-Induced Toxicities. (17th March 2021) - Fatima, Syeda; Aslam, Nazia; Khalid, Sofia; Ullah, Kalim; Abbas, Khizar; Hussain, Shahzad; Shah, Syed Sajid Hussain; Qureshi, Zia-Ur-Rahman; Qayum, Mughal; Asad, Muhammad Hassham Hassan Bin
Abstract : Snakebite is one of the most neglected diseases of developing countries. Deaths due to snakebite envenoming are quite high in Pakistan, and many deaths are caused by Echis carinatus envenomation. Traditional use of medicinal plants against snakebites is a common practice in Pakistan due to countless benefits. The current study was performed with the objective to evaluate eighteen Pakistani medicinal plants inhibitory potential against hyaluronidase and alkaline phosphatase enzymes of Pakistani Echis carinatus venom. Hyaluronidase activity (0.2-1.6 mg/0.1 mL) and alkaline phosphatase activity (0.1-0.8 mg/0.1 mL) were measured in dose-dependent manner. Crude methanolic extracts of medicinal plants were used for in vitro investigation of their inhibitory activity against toxic enzymes. All active plants were fractioned using different solvents and were again analyzed for inhibitory activity of same enzymes. Results indicated all plants were able to neutralize hyaluronidase that Swertia chirayita (Roxb. ex Flem.) Karst., Terminalia arjuna Wight and Arn, Rubia cordifolia Thumb., and Matthiola incana (L.) R.Br. inhibited maximum hyaluronidase activity equivalent to standard reference (p > 0.5 ). Pakistani medicinal plants are dense with natural neutralizing metabolites and other active phytochemicals which could inhibit hyaluronidase activity of Pakistani Echis carinatus venom. Further advanced studies at molecular level could lead us to an alternative for envenoming of Pakistani Echis carinatus venom.